Effects of Reduced Kidney Function Because of Living Kidney Donation on Left Ventricular Mass. Issue 2 (February 2017) - Altmann, Ursula; Böger, Carsten A.; Farkas, Stefan; Mack, Matthias; Luchner, Andreas; Hamer, Okka W.; Zeman, Florian; Debl, Kurt; Fellner, Claudia; Jungbauer, Carsten; Banas, Bernhard; Buchner, Stefan
Abstract : Living kidney donation is associated with a small but significant increase in cardiovascular mortality. In addition, mildly decreased kidney function is associated with an increase of left ventricular mass and with cardiovascular disease in patients with chronic kidney disease. To investigate this association, we evaluated the impact of mildly decreased kidney function after living kidney donation on subclinical cardiac structural and functional changes. In this prospective cohort study, cardiac and renal magnetic resonance imaging and laboratory analyses were performed in 23 living kidney donors (mean age 54±10 years, 52% male) before donation and at 4 and 12 months after nephrectomy. Mean estimated glomerular filtration rate was 102±15 mL min −1 1.73 m −2 before donation and 70±13 mL min −1 1.73 m −2 at 12 months ( P <0.001). Left ventricular mass increased from 112±22 to 115±23 g ( P <0.001). In addition, heart rate was significantly increased (65±7 to 74±14; P =0.04). Concurrently, kidney and adrenal gland volume increased from 163±33 to 195±34 mL ( P <0.001) and from 7.6±2.2 to 8.4±2.4 mL ( P =0.032), respectively, as did procollagen type III (Δ0.11 ng/mL, P <0.001) and not N-terminal probrain natriuretic peptide (Δ14 pg/mL, P =0.25). The mild decrease in kidney function after living kidney donation leads to a significant but clinically negligible increase in left ventricular mass 12 months after living kidney donation. This study of a longitudinal analysis of living kidney donors provides direct evidence of a kidney–heart link. Abstract : Supplemental Digital Content is available in the text.